Aplicações de modelos de procura para bens duráveis de baixa liquidez - Studart, Marcus Eduardo Mathias (2009)
I use Search models to study decentralized markets of durable goods. I explore the concept of market liquidity of Lippman and McCall (1986) and show that the theory of optimal search is useful to address the following issues: What governs the time required to make a transaction on these markets? What is the relationship between the price of goods and the time required to make transactions? Why is optimal to wait to make a transaction in markets where individuals discount future utility? What is the socially optima search level? Two specifications are used, the traditional model of job search and a version of Krainer and LeRoy (2001) model.